STUDY ON THE THERMAL DECOMPOSITION KINETIC OF HMX AND OCFOL EXPLOSIVES - Toàn (Journal of Military Science and Technology, 2021)
The thermal decomposition kinetics of Octogen and Ocfol (phlegmatized HMX) explosives have been studied by thermal gravimetric analysis (TG/DTG) and differential thermal analysis (DTA) techniques in the different heating rates. The thermal decomposition kinetic parameters were determined by traditional methods (Kisinger method, Ozawa method) and model-free method (Kisinger-Akahira-Sunose method). Results showed that the activation energy of thermal decomposition of HMX and Ocfol explosives were in the range (294-336) and (216-239) kJ/mol, respectively. In addition, decomposition rate constants showed that HMX is more thermostable than Ocfol. The kinetic parameters for the thermal decomposition of HMX in the low temperature region are in good agreement with data, obtained in the region of the combustion surface temperatures.